An institutionalist perspective on the future of the capitalist world-economy - Özçelik, Emre; Özveren, Eyüp (Journal of Economic Issues, 2006)
The term world-economy in our title must have already given a hint to the careful reader of our purpose in writing this paper: We intend to bridge institutional economics with world-systems analysis in order to enhance the global applicability of the former. World-economy is a term used by Fernand Braudel and Immanuel Wallerstein and means a space defined by the existence of a single division of labor (coexistent with multiple States) whereas world economy would indicate the arithmetic summation of national economies each of which ... In this paper, we elaborate Polanyi's concept of embeddedness so as to construct an institutionalist framework to understand the contemporary world-economy. We contend that embeddedness can be deployed to analyze the so-called "global governance model" (GGM) as the most recent liberal recipe.
Economics
Keywords: embeddedness; global governance model; world-economy